Review: Searching for a Democratic Equalizer: How Citizenship Education Moderates Inequalities in Internal Political Efficacy (PhD by Joke Matthieu, Vrije Universiteit Brussel) - Erzeel, Silvia (Politics of the Low Countries, 2025)
Gender and social inequalities in internal political efficacy have long been persistent challenges in the domain of political engagement. Joke Matthieu’s PhD thesis addresses the critical question of why these inequalities endure and examines avenues for enhancing young people’s internal political efficacy.